2019
DOI: 10.1002/cncr.32380
|View full text |Cite
|
Sign up to set email alerts
|

Practices and perceptions regarding intravenous opioid infusion and cancer pain management

Abstract: BACKGROUND: In view of the recent opioid crisis, ways to promote safe and effective opioid-related practices are needed. Faster intravenous (iv) opioid infusion rates can result in increased adverse effects and risk for nonmedical opioid use. Data on best practices regarding safe iv opioid administration for cancer pain are limited. This study examined iv opioid bolus infusion practices and perceptions about opioids in cancer pain among 4 groups of inpatient oncology nurses. METHODS: An anonymous cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The prevalence of NMOU in the inpatient setting is presumably comparable to the outpatient oncologic settings since it is the same cancer patient population who are eventually hospitalized for management of acute issues. Moreover, patients are more likely to display NMOU behaviors in the inpatient setting due to access to parenteral opioids which may increase the peak serum concentration in the brain more rapidly, leading to heightened reward (Arthur et al 2019). It is therefore critical that inpatient clinical teams utilize risk mitigation strategies to the same degree as in the outpatient settings (Chou 2009;Dowell et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of NMOU in the inpatient setting is presumably comparable to the outpatient oncologic settings since it is the same cancer patient population who are eventually hospitalized for management of acute issues. Moreover, patients are more likely to display NMOU behaviors in the inpatient setting due to access to parenteral opioids which may increase the peak serum concentration in the brain more rapidly, leading to heightened reward (Arthur et al 2019). It is therefore critical that inpatient clinical teams utilize risk mitigation strategies to the same degree as in the outpatient settings (Chou 2009;Dowell et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The International Association for the Study of Pain outlined important clinical obstacles for effective pain management, such as lack of knowledge (Treede, 2018 ), opioid phobia towards opioid addiction and respiratory depression (Uslu Sahan & Terzioglu, 2017 ), lack of effective interdisciplinary communication (Glowacki, 2015 ), medical team's reluctance to prescribe opioids (Arthur et al, 2019 ), the delay of opioid storage protocol (Guest et al, 2017 ), lack of pain assessment and protocols and nursing workload (Kahsay & Pitkäjärvi, 2019 ). It was also suggested that nursing pharmacology curriculum may not adequately equip undergraduate nurses with pain management skills (Lokapur et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 2015 Quality of Death Index ranked many Middle Eastern and East African countries at the bottom of the scale in terms of palliative care, including pain management [7]. Several factors were blamed for inadequate pain control, such as inadequate knowledge [8], lack of pain assessment due to nurses' overload [9], reluctance to prescribe opioids by healthcare providers [10], and fear of opioid side effects and addiction [11,12]. Therefore, proper training of healthcare providers in cancer pain management is needed to improve their knowledge and skills and to consider the patient's special needs at different ages and disease stages.…”
Section: Introductionmentioning
confidence: 99%